Fostering Cultural Humility among Pre-Service Teachers: Connecting with Children and Youth of Immigrant Families through Service-Learning - Lund, Darren; Lee, Lianne (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
This article documents a community-initiated service-learning project within a teacher education program. A social justice model guided the initiative to raise critical awareness on power and privilege while countering deficit-model thinking. Partnering with community agencies serving immigrant children and youth, the faculty researcher worked with an office for community-engaged learning. Data included pre- and post-experience interviews with pre-service candidates. Findings showed benefits from this justice-based approach in improving self-awareness, appreciating the strengths of immigrant children and youth, and an increased sense of cultural humility in pre-service teachers.